The Role of The Wire Media in the Jammu-Kashmir Conflict through a Peace Journalism Perspective - Lukuaka, Defrida Suzana; Alexandra, Halomoan Freddy Sitinjak; Saragih, Herlina Juni Risma; Widodo, Pujo (representamen, 2025)
The conflict in the Jammu-Kashmir region has become one of the longest-running conflicts in Indian history. The Jammu-Kashmir region is an area located between India and Pakistan. Since 1948, this conflict has had many impacts both domestically in India and Pakistan, and has involved other countries in mediation and conflict resolution efforts for Jammu-Kashmir. In addition to political involvement in mediation and resolution efforts, there is also the involvement of mass media as a communication and information tool for the parties involved. The Wire is one of the mass media outlets actively covering and writing news about the Jammu-Kashmir conflict in India. In the world of journalism itself, there is a new concept called Peace Journalism. The concept of peace journalism emphasizes the role of mass media as a third party in a conflict, or in other words, as a mediator for the parties involved or affected by the conflict. The Wire is a media outlet that consistently covers and writes news related to the Jammu-Kashmir Conflict. From this consistency, it is necessary to consider The Wire's role as a medium in conveying the aspirations of the Kashmiri people and the responses of the Indian-Pakistani governments in media openness. This journal will discuss how The Wire carries out its role as a mass communication and information medium in the Jammu-Kashmir conflict through the perspective of Peace Journalism. To obtain descriptive results, the author uses a literature review method, utilizing literature sources such as books, scientific journals, and internet sites relevant to the topic discussed. From this method, it was found that The Wire is included in the media that uses the concept of peace journalism in its reporting related to the Jammu-Kashmir conflict. However, in using the concept of peace journalism, The Wire does not lose its critical stance towards Indian government policies related to the Jammu-Kashmir conflict. This research is expected to provide insights into the role of mass media in conflict through the perspective of peace journalism. Keywords : Conflict, Jammu-Kashmir, The Wire, Mass Media, Peace Journalism